Local IgE in non‐allergic rhinitis. Issue 5 (16th April 2015) - Campo, P.; Rondón, C.; Gould, H. J.; Barrionuevo, E.; Gevaert, P.; Blanca, M.
Summary: Local allergic rhinitis (LAR) is characterized by the presence of a nasal Th2 inflammatory response with local production of specific IgE antibodies and a positive response to a nasal allergen provocation test (NAPT) without evidence of systemic atopy. The prevalence has been shown to be up to 25% in subjects affected with rhinitis with persistence, comorbidity and evolution similar to allergic rhinitis. LAR is a consistent entity that does not evolve to allergic rhinitis with systemic atopy over time although patients have significant impairment in quality of life and increase in the severity of nasal symptoms over time. Lower airways can be also involved. The diagnosis of LAR is based mostly on demonstration of positive response to NAPT and/or local synthesis of specific IgE. Allergens involved include seasonal or perennial such as house dusts mites, pollens, animal epithelia, moulds (alternaria) and others. Basophils from peripheral blood may be activated by the involved allergens suggesting the spill over of locally synthesized specific IgE to the circulation. LAR patients will benefit from the same treatment as allergic patients using antihistamines, inhaled corticosteroids and IgE antagonists. Studies on immunotherapy are ongoing and will determine its efficacy in LAR in terms of symptoms improvement and evolution of the natural course of the disease.